Gammaherpesvirus infection modulates the temporal and spatial expression of SCGB1A1 (CCSP) and BPIFA1 (SPLUNC1) in the respiratory tract - Leeming, G; Kipar, A; Hughes, D; Bingle, L; Bennett, E; Moyo, N; Tripp, R; Bigley, A; Bingle, C; Sample, J; Stewart, J (Springer Nature, 2014)
Murine γ-herpesvirus 68 (MHV-68) infection of Mus musculus-derived strains of mice is an established model of γ-herpesvirus infection. We have previously developed an alternative system using a natural host, the wood mouse (Apodemus sylvaticus), and shown that the MHV-68 M3 chemokine-binding protein contributes significantly to MHV-68 pathogenesis. Here we demonstrate in A. sylvaticus using high-density micro-arrays that M3 influences the expression of genes involved in the host response including Scgb1a1 and Bpifa1 that encode potential innate defense proteins secreted into the respiratory tract. Further analysis of MHV-68-infected animals showed that the levels of both protein and RNA for SCGB1A1 and BPIFA1 were decreased at day 7 post infection (p.i.) but increased at day 14 p.i. as compared with M3-deficient and mock-infected animals. The modulation of expression was most pronounced in bronchioles but was also present in the bronchi and trachea. Double staining using RNA in situ hybridization and immunohistology demonstrated that much of the BPIFA1 expression occurs in club cells along with SCGB1A1 and that BPIFA1 is stored within granules in these cells. The increase in SCGB1A1 and BPIFA1 expression at day 14 p.i. was associated with the differentiation of club cells into mucus-secreting cells. Our data highlight the role of club cells and the potential of SCGB1A1 and BPIFA1 as innate defense mediators during respiratory virus infection.